The Influence of Herding Behavior and Overconfidence on Sustainable Investment Decisions (A Study of Generation Z Retail Investors in the Greater Bandung Area) - Agung Rizki Anugrah; Frido S. Simatupang (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the effect of herding behavior and overconfidence on sustainable investment decisions among Generation Z retail investors in the Greater Bandung area. The background of this research is based on the increasing number of young investors influenced by digital accessibility and the potential emergence of behavioral biases in investment decision-making. This study employs a quantitative approach with descriptive and associative research designs. Data were collected through an online questionnaire from 107 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS, including validity, reliability, and classical assumption tests. The results indicate that herding behavior and overconfidence have a significant effect, both partially and simultaneously, on sustainable investment decisions with a negative direction. This implies that higher levels of these biases reduce the likelihood of investors making sustainable investment decisions. The findings highlight the importance of managing behavioral biases, improving financial literacy, and enhancing investor awareness in considering long-term and sustainability aspects in investment decisions.